Characterization of distinctiveness in existing genetic resources of pumpkin (Cucurbita moschata Duch ex Poir.) by using morphological markers - Akhil Kumar Chaudhary; C. N. Ram; Santosh Kumar; Virendra Kumar; Shyam Praksah; Suman Poonia (The Bioscan, 2025)
The morphological characterization of pumpkin (Cucurbita moschata Duch ex Poir.) was undertaken to evaluate genetic diversity and generate valuable information for breeding programmes. A total of 52 genotypes—including 15 promising parental lines and 36 hybrids—were assessed at Acharya Narendra Deva University of Agriculture and Technology, Ayodhya, Uttar Pradesh, during the Zaid seasons of 2024 and 2025. Morphometric observations were recorded on 14 traits, including leaf shape, fruit characteristics and seed shape. Significant genetic variation was observed across genotypes, particularly in fruit traits such as shape, skin colour and flash color structure. The findings underscore the importance of genetic diversity in pumpkin for developing improved varieties with desirable agronomic traits. This study establishes a foundation for crop improvement.